The Effect of Perceived Service Quality and Perceived Value on Loyalty with Customer Satisfaction Mediation (Case Study on Simadu Savings Customers of PT BPR BKK Tasikmadu (Perseroda) - Andriani Kurniawati; Alimuddin Rizal Rivai (Universitas KH. Abdul Chalim Mojokerto, 2026)
Customers play a vital role in the bank's progress. One form of this role is loyalty. Customer loyalty can be formed through perceived service quality, perceived value, and satisfaction. This study was conducted on Simadu savings customers of PT BPR BKK Tasikmadu (Perseroda). The sample was determined using the Slovin formula. The number of respondents was 110 Simadu savings customers. The data were analyzed using validity tests (KMO > 0.5 and component matrix > 0.4) and reliability tests (Cronbach's Alpha > 0.7). Multiple linear regression was used to test the model and hypothesis. Tests included the coefficient of determination, F test, and significance test (p < 0.05). This study also used satisfaction as a mediating variable. The Sobel test was used to see the mediation effect (significant if p < 0.05). The results of model I have 2 hypothesis tests, namely: a positive and significant influence between perceived service quality on satisfaction (β = 0.602; sig = 0.00 <0.05), this shows that the better the perceived service quality, the more it will increase customer satisfaction. Furthermore, there is a positive and significant influence between perceived value on satisfaction (β = 0.269; sig = 0.00 <0.05), this explains that the suitability of values ​​felt by customers will increase customer satisfaction at the bank. In model II, there are 3 hypothesis tests, namely: a positive and significant influence between perceived service quality on loyalty (β = 0.260; sig = 0.00 <0.05) this shows that the more appropriate the perceived service quality, the more it will encourage the achievement of customer loyalty. Furthermore, perceived value has a positive effect on satisfaction (β = 0.139; sig = 0.08 <0.05), indicating that the greater the suitability of the values ​​perceived by customers, the greater the customer loyalty will be. Satisfaction has the greatest influence on loyalty as proven by the value (β = 0.609; sig = 0.00 <0.05), indicating that with customer satisfaction as the foundation for creating satisfaction, satisfied customers will strive to maintain their loyalty and even recommend to colleagues. This study also uses mediation, which in its testing uses the Sobel test. The results of the Sobel test on the influence of perceived service quality on loyalty with satisfaction mediation show (sig = 0.00 < 0.05) which means that satisfaction mediates the influence of perceived service quality on loyalty. Furthermore, the results of the Sobel test on the influence of perceived value on loyalty with satisfaction mediation show (sig = 0.00 < 0.05) which means that satisfaction mediates the influence of perceived value on loyalty.